Heavy Metal Pollution of River Hasdeo of Chhattisgarh at Different Places in Korba District - Thakur, Kiran; Yadav, Praveen (International Journal of Computer Sciences and Engineering, 2025)
Continuous discharge of the organic pollutants from different industry into the environment has resulted in building up their high levels in various aquatic systems. River Hasdeo is largest tributary of Mahanadi, serves as the major sources of municipal water supplies for domestic, irrigation and industrial purpose for korba town. Samples of water at four location from the river were collected and analyzed for different physicochemical parameters and 9 heavy metal concentration. Throughout the study, the result from the current investigation revealed that most of the physical and chemical parameters were exceeded from their prescribed limits which suggests all the samples are suitable for irrigation purpose but not for drinking use. Of course, stringent control is further required on the physico chemical parameters of the effluents